PI3K Orchestrates T Follicular Helper Cell Differentiation in a Context Dependent Manner: Implications for Autoimmunity - Preite, Silvia; Huang, Bonnie; Cannons, Jennifer L.; McGavern, Dorian B.; Schwartzberg, Pamela L. (Frontiers in Immunology, 2019)
T follicular helper (Tfh) cells are a specialized population of CD4+ T cells that provide help to B cells for the formation and maintenance germinal centers, and the production of high affinity class-switched antibodies, long-lived plasma cells and memory B cells. As such, Tfh cells are essential for the generation of successful long-term humoral immunity and memory responses to vaccination and infection. Conversely, overproduction of Tfh cells has been associated with the generation of autoantibodies and autoimmunity. Data from gene-targeted mice, pharmacological inhibitors, as well as studies of human and mice expressing activating mutants have revealed that PI3K is a key regulator of Tfh cell differentiation, acting downstream of ICOS to facilitate inactivation of FOXO1, repression of Klf2 and induction of Bcl6. Nonetheless, here we show that after acute LCMV infection, WT and activated-PI3K mice (Pik3cdE1020K/+) show comparable ratios of Tfh:Th1 viral specific CD4+ T cells, despite higher polyclonal Tfh cells in Pik3cdE1020K/+ mice. Thus, the idea that PI3K activity primarily drives Tfh cell differentiation may be an oversimplification and PI3K-mediated pathways are likely to integrate multiple signals to promote distinct effector T cell lineages. The consequences of dysregulated Tfh cell generation will be discussed in the context of the human primary immunodeficiency “Activated PI3K-delta Syndrome” (APDS), also known as “p110 delta-activating mutation causing senescent T cells, lymphadenopathy and immunodeficiency” (PASLI). Overall, these data underscore a major role for PI3K signaling in the orchestration of T lymphocyte responses.